Summary of COVID-19 vaccine-related erythema multiforme at Kindai University Hospital, Japan - Watanabe, Keiko; Nakashima, Chisa; Matsuo, Ayako; Kato, Maiko; Yanagihara, Shigeto; Oiso, Naoki; Otsuka, Atsushi (Trends in Immunotherapy, 2022)
The recently extended use of mRNA vaccines due to the COVID-19 pandemic has allowed the description of multiple cutaneous adverse events including local injection site reactions, urticaria, and morbilliform eruptions. COVID-19 vaccine-related cutaneous reaction patterns can be divided into type Ⅰ hypersensitivity reactions, type Ⅳ hypersensitivity reactions, autoimmune-related, and functional angiopathies based on pathogenesis. Erythema multiforme (EM), a type IV hypersensitivity reaction, has also been reported from several centers. We experienced the remarkable improvement of COVID-19 vaccine-related EM with systemic administration of prednisolone and summarized six cases experienced in our department.